2018
DOI: 10.1128/aac.00193-18
|View full text |Cite
|
Sign up to set email alerts
|

Self-Resistance during Muraymycin Biosynthesis: a Complementary Nucleotidyltransferase and Phosphotransferase with Identical Modification Sites and Distinct Temporal Order

Abstract: Muraymycins are antibacterial natural products from spp. that inhibit translocase I (MraY), which is involved in cell wall biosynthesis. Structurally, muraymycins consist of a 5'--glycyluridine (GlyU) appended to a 5″-amino-5″-deoxyribose (ADR), forming a disaccharide core that is found in several peptidyl nucleoside inhibitors of MraY. For muraymycins, the GlyU-ADR disaccharide is further modified with an aminopropyl-linked peptide to generate the simplest structures, annotated as the muraymycin D series. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“… 7 , 9 If the peptide of muraymycins is l -leucine and there is a hydroxyl group in the 2″-position of the ADR moiety, muraymycin will be classified as muraymycin D2 (MD2) ( Figure 1 ). 9 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 9 If the peptide of muraymycins is l -leucine and there is a hydroxyl group in the 2″-position of the ADR moiety, muraymycin will be classified as muraymycin D2 (MD2) ( Figure 1 ). 9 …”
Section: Introductionmentioning
confidence: 99%
“…LCMS analysis of the new peak yielded an (M + H) + ion at m/z = 449.1463 (Figure 8C), which is consistent with the molecular formula for ADR-GlyU disaccharide ( 17a ) [expected (M + H) + ion at m/z = 449.1442 for C 16 H 24 N 4 O 11 ]. To simplify the analytical identification of the product, 17a was prepared by chemical synthesis (Figures S8-S12); 30 analysis of the Mur19-catalyzed reaction revealed the new peak co-eluted with, and had identical UV and MS spectroscopic properties to, authentic 17a . The data are therefore consistent with the functional assignment of Mur19 as a 12 : 15a 5-amino-5-deoxyribosyltransferase.…”
Section: Resultsmentioning
confidence: 99%
“…The stereoselective synthesis of the disaccharide 17a followed a previously described procedure, 30 which is based on the methodology first reported by Hirano et al 4,34,35 1 H NMR (500 MHz, D 2 O) δ 7.74 (d, J = 8.0 Hz, 1H), 5.87 (d, J = 8.0 Hz, 1H), 5.81 (d, J = 2.7 Hz, 1H), 5.17 (s, 1H), 4.50 (br s, 1H), 4.35 (dd, J = 5.0, 2.7 Hz, 1H), 4.18–4.26 (m, 2H), 4.08–4.17 (m, 3H), 3.88 (br s, 1H), 3.25–3.38 (m, 1H), 3.06–3.15 (m, 1H); 13 C NMR (126 MHz, D 2 O) δ 167.4, 152.3, 141.7, 109.0, 102.0, 91.0, 84.7, 79.1, 77.2, 75.0, 73.1, 72.0, 69.3, 57.2, 42.5; HRMS (ESI/Q-TOF) m/z: [M + H] + Calcd for C 16 H 25 N 4 O 11 449.1520; Found 449.1462; IR (ATR) ν 3139, 2935, 2365, 2336, 1703, 1684, 1627, 1510, 1470, 1395, 1272, 1197, 1121, 1051, 1005, 819, 796, 720; UV (H 2 O) λ max (log ε) 202 (2.13), 262 (2.10); mp 172 °C (decomposition); TLC R f 0.05–0.16 (5:2:1 i -PrOH-H 2 O-AcOH as saturated NaCl solution); [α] D 20 +3.8 ( c 0.90, H 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…Resistance genes are often carried by the same gene cluster of the antibiotic biosynthetic enzymes, and their expression is temporally coupled. Indeed, antibiotic producer cells need to express resistance determinants prior to, or concomitantly with, synthesis of the antibiotic molecule (26, 27). In recent years, the analysis of several genomes suggested that microorganisms produce only a fraction of the secondary metabolites that they encode, and new approaches have been used to identify biosynthetic gene clusters whose expression can be induced.…”
Section: Discussionmentioning
confidence: 99%